2013
DOI: 10.1111/puar.12136
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative Innovation: A Viable Alternative to Market Competition and Organizational Entrepreneurship

Abstract: Abstract:There are growing pressures for the public sector to be more innovative but considerable disagreement about how to achieve it. This paper uses institutional and organizational analysis to compare three major but different public innovation strategies. The paper commences by confronting the myth that the market-driven private sector is more innovative than the public sector by showing that both sectors have a number of barriers as well as drivers of innovation, some of which are similar while others ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
488
1
53

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 518 publications
(550 citation statements)
references
References 69 publications
8
488
1
53
Order By: Relevance
“…First, elected politicians have been pivotal in shaping this agenda, top-down, through strong Ministerial leadership that has stimulated confidence amongst officials throughout the bureaucracy. The evidence presented here supports the view that a productive relationship between policymakers and administrators is beneficial in securing policy innovation (Hartley et al, 2013). Political leaders were pivotal in setting the agenda, while public managers assumed the role of policy innovators (Polsby, 1984).…”
Section: Innovations In Policy -Examining the Outcomessupporting
confidence: 64%
See 2 more Smart Citations
“…First, elected politicians have been pivotal in shaping this agenda, top-down, through strong Ministerial leadership that has stimulated confidence amongst officials throughout the bureaucracy. The evidence presented here supports the view that a productive relationship between policymakers and administrators is beneficial in securing policy innovation (Hartley et al, 2013). Political leaders were pivotal in setting the agenda, while public managers assumed the role of policy innovators (Polsby, 1984).…”
Section: Innovations In Policy -Examining the Outcomessupporting
confidence: 64%
“…There was also a view that some of the tough and frank discussions required to strike deals would be extremely difficult to have on the record and informal governance provided a safe space 'where we wouldn't want the public or our colleagues monitoring our every conversation' (DCLG official). Here informality was often used to overcome political or institutional barriers and to break deadlocks (Hartley et al, 2013). Whitehall officials felt that informal working had been largely positive, an observation supported by Localis and Grant Thornton (2015, 16) who suggested that '72% of local actors had found the discussions with central government constructive and positive'.…”
Section: Innovations In Politics -Examining the Processmentioning
confidence: 91%
See 1 more Smart Citation
“…However, to date, there has been little discussion of the processes of social innovation through which social prescribing has been adopted and diffused across the UK. The idea of collaborative innovation is helpful here because it highlights the importance of multi-actor collaboration during the development and implementation of a new policy (Hartley et al, 2013). In particular, it emphasises the involvement of 'downstream' actors, including voluntary and community organisations and service users, alongside 'upstream' policy stakeholders, in the creation and diffusion of novel and bold solutions to previously intractable and 'wicked' problems (Ansell et al, 2017).…”
Section: Processes Of Collaborative Innovationmentioning
confidence: 99%
“…140; 15], бросающих вызов текущим установленным методам и навыкам производства [16]. В числе инноваций, играющих важную роль как для государственного, так и для частного сектора [17], приоритетными являются до-стижения 4-й промышленной революции, внедрение которых стимулируется государ-ственными закупками инновационной продукции.…”
unclassified